Serum asprosin levels in patients with retinopathy of prematurity - Yardim, Meltem; Celik, Fatih; Oruc, Yavuz; Kayalp, Damla; Beyazyildiz, Ozlem; Yesilirmak, Didem Cemile; Aydin, Suleyman (Walter de Gruyter Gmbh, 2022)
Objectives This study was aimed to investigate the diagnostic values of serum levels of asprosin and neutrophil gelatinase-associated lipocalin (NGAL) in Retinopathy of prematurity (ROP) and to assess the role of these biomarkers on the development and progression of the condition. Methods This study was carried out from April 2020 to February 2021 in the department of ophthalmology of a tertiary hospital in Turkey. Thirty patients diagnosed with ROP and 30 healthy newborns were included the study. Serum NGAL and asprosin levels were determined via ELISA. Results The median serum NGAL levels were found to be similar between the ROP group and the control group (p=0.595). Median asprosin levels were significantly higher in patients diagnosed with ROP [46.58 (12.70-142.28) ng/mL] compared to healthy subjects [13.05 (10.92-17.73) ng/mL] (p=0.001). The optimal cut-off value of asprosin by ROC analysis was 30 ng/mL (AUC: 0.754, p=0.001) for diagnosing ROP. Serum asprosin levels were positively correlated with serum ALP levels and inversely correlated with gestational week, uric acid and AST values (all, p<0.005). Conclusions Our results demonstrated that asprosin, but not NGAL, could be a biomarker for the diagnosis of ROP.
Keywords: asprosin; diagnostic; neutrophil gelatinase-associated lipocalin; prematurity; retina; retinopathy of prematurity